Acute-lethal toxicity (LC50) effect of terminalia catappa linn. Leaves extract on oreochromis niloticus (Red nile tilapia) juveniles under static toxicity exposure - Yunus, Kamaruzzaman; Jaafar, Ainatul Mardhiah; John, Akbar (Scientific Publishers, 2019)
Presnt study was conducted to assess the toxic effect of Terminalia catappa leaf extract on the red Nile tilapia (Oreochromis niloticus) juveniles under static toxicity exposure (96 h exposure). Different concentration of leaf extracts was administered (700 ppm, 800 ppm, 900 ppm, 1000 ppm and 1100 ppm) on red tilapia juveniles in 5 experimental tanks in triplicate. A total of 10 red Nile tilapia juveniles per tank were used as experimental specimens. Median lethal concentration value, LC50 was determined and juvenile behavioral changes were documented. Results showed that the LC50 value was 900 ppm at a random range of time up to 96 h. Present study will be beneficial in considering the proper utilization of T. catappa leaf as potential antibacterial agent in conventional aquaculture practices.